1987
DOI: 10.1001/archderm.1987.01660340118032
|View full text |Cite
|
Sign up to set email alerts
|

Adult Kawasaki Syndrome

Abstract: Kawasaki syndrome (KS) is an idiopathic, acute, febrile, exanthemous illness that primarily affects infants and children. We describe a 20-year-old black woman who fulfilled the clinical criteria for the diagnosis of KS and excluded other possible causes. In addition, we reviewed data on 21 patients with adult KS reported in the English literature and accepted ten cases as representing this syndrome. The epidemiologic, clinical, laboratory, and pathologic features of the 11 cases representing adult KS are disc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(7 citation statements)
references
References 29 publications
1
6
0
Order By: Relevance
“…However, platelet counts in these patients were still within the accepted "normal" range, and therefore, reliable cut-off levels for differential diagnosis between KDSS and TSS could not be defined. 32,33 The absence of a clear diagnostic criterion based on platelet count is corroborated by previous studies, which have reported an inconsistent association between thrombocytosis or thrombocytopenia and KDSS. As an example, although Kanegaye et al 6 reported significantly lower platelet counts in 13 patients with KDSS (148 × 10 3 per μL) compared with patients with KD without shock (410 × 10 3 per μL), 4 patients in their study group had a normal platelet count before IVIG therapy, and the level for 2 other patients were not reported.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…However, platelet counts in these patients were still within the accepted "normal" range, and therefore, reliable cut-off levels for differential diagnosis between KDSS and TSS could not be defined. 32,33 The absence of a clear diagnostic criterion based on platelet count is corroborated by previous studies, which have reported an inconsistent association between thrombocytosis or thrombocytopenia and KDSS. As an example, although Kanegaye et al 6 reported significantly lower platelet counts in 13 patients with KDSS (148 × 10 3 per μL) compared with patients with KD without shock (410 × 10 3 per μL), 4 patients in their study group had a normal platelet count before IVIG therapy, and the level for 2 other patients were not reported.…”
Section: Discussionsupporting
confidence: 55%
“…[19][20][21][22][23][24][25] Therefore, we conducted a retrospective medical chart review to compare and contrast the clinical features of patients with KDSS and TSS, with the aim of identifying specific features that would inform early differential diagnosis between these 2 conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with no evidence of aneurysm or ectasia at the 1-year evaluation are not likely to benefit from further repeated echocardiography, although patients with transient coronary artery ectasia early in the illness may be followed up at 3-to 5-year intervals. 19,20 Magnetic resonance imaging can also assess coronary morphology with low temporal resolution (20-50 ms). The 3-dimensional spatial resolution achievable is marginal for coronary arterial imaging and is not as reliable as multidetector computed tomography.…”
Section: Discussionmentioning
confidence: 99%
“…The disease is most commonly seen in children younger than 5 years of age and is distinctly uncommon after adolescence. 1 There is no diagnostic laboratory test for KD. However, elevated platelet counts are a consistent feature of this particular illness.…”
mentioning
confidence: 99%